1999
DOI: 10.1006/jfls.1999.0236
|View full text |Cite
|
Sign up to set email alerts
|

Motions, Forces and Mode Transitions in Vortex-Induced Vibrations at Low Mass-Damping

Abstract: These experiments, involving the transverse oscillations of an elastically mounted rigid cylinder at very low mass and damping, have shown that there exist two distinct types of response in such systems, depending on whether one has a low combined mass-damping parameter (low m* ), or a high mass-damping (high m* ). For our low m* , we "nd three modes of response, which are denoted as an initial amplitude branch, an upper branch and a lower branch. For the classical Feng-type response, at high m* , there exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
579
8
20

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 911 publications
(683 citation statements)
references
References 39 publications
76
579
8
20
Order By: Relevance
“…The jumps between the tree branches were associated with changes in the phase angle between the motion and the excitation force. Khalak & Williamson (1999) concluded that the maximum vibration amplitude is related to the product m * ζ, while the width of the range U r where synchronization occurs is directly related to the value of m * for cases of the same m * ζ, as can be observed in (Vertical axes represent A * and horizontal axes represent U r ), from Khalak & Williamson (1999) The maximum amplitude achievable by a certain system is something that has captured the interest of researches working on VIV. Gri n & Ramberg (1982) published a work where the relationship between the maximum amplitude recorded for a system was plotted against a parameter called reduced damping which was based on the mass an the damping ratio of the system.…”
Section: Typical Viv Responsementioning
confidence: 96%
See 1 more Smart Citation
“…The jumps between the tree branches were associated with changes in the phase angle between the motion and the excitation force. Khalak & Williamson (1999) concluded that the maximum vibration amplitude is related to the product m * ζ, while the width of the range U r where synchronization occurs is directly related to the value of m * for cases of the same m * ζ, as can be observed in (Vertical axes represent A * and horizontal axes represent U r ), from Khalak & Williamson (1999) The maximum amplitude achievable by a certain system is something that has captured the interest of researches working on VIV. Gri n & Ramberg (1982) published a work where the relationship between the maximum amplitude recorded for a system was plotted against a parameter called reduced damping which was based on the mass an the damping ratio of the system.…”
Section: Typical Viv Responsementioning
confidence: 96%
“…Experimental results for the dynamic response in terms of displacement amplitude and frequency of oscillation, as well as mean drag and uctuating lift coe cients were measured for a plain cylinder and the other suppressor models. The validation of the plain cylinder was based on the papers of Khalak & Williamson (1977,1999. Figure 5.1 presents the displacement amplitudes and frequencies of oscillation of a plain cylinder compared with the results obtained by Khalak & Williamson (1997).…”
Section: Validation Of a Plain Cylindermentioning
confidence: 99%
“…After manipulation, the response amplitude and frequency can be formulated using nondimensional parameters (Khalak and Williamson, 1999), …”
Section: Elastically Supported Circular Cylindersmentioning
confidence: 99%
“…O trabalho de Skop & Balasubramanian (1997) revisitou as equações do modelo de oscilador anteriormente apresentadas em Skop & Griffin (1975) e, com base nos estudos mais recentes, redefiniu a maneira como as predições de amplitude seriam realizadas. A partir deste trabalho e o de Khalak & Williamson (1999) o parâmetro mais aceito para a avaliação da amplitude máxima de resposta foi (m * + C P OT a )ζ (calculado de acordo com a Tabela 2.2).…”
Section: Parâmetro Símbolo Expressãounclassified
“…Numa abordagem mais voltada ao estudo de VIV, como a utilizada em Khalak & Williamson (1999), o valor de amortecimento (ζ) é avaliado conforme o apresentado anteriormente na Tabela 2.2, ou seja:…”
Section: Ensaio De Decaimentounclassified